Assessment of antiviral activity and mechanism of rhein on newcastle disease virus (La Sota strain IV) in vitro. Issue 5 (4th March 2022) - Hu, Yanchun; Okyere, Samuel Kumi; Xu, Ruiguang; Peng, Guangneng; Ren, Zhihua; Deng, Junliang; Jia, Yan
Abstract: Current research is focused on the development of drug candidates from natural products. Rhein a Traditional Chinese Medicine (TCM) from Polygonaceae (rhubarb) has exhibited antioxidant, anti-inflammatory and anticancer activities, however no work has reported its antiviral potential, thus this study was performed to investigate the antiviral activities of rhein on new castle disease virus (NDV) in vitro. NDV infection of chicken embryo fibroblasts (CEFs) was prepared using 10-day-old specific pathogen free chicken embryos. Cytotoxicity and anti-viral activities of rhein were assessed using the MTT method. The interaction between NDV and cell membrane proteins were also detected using virus overlay protein binding assay (VOPBA). In addition NDV genes expressions in CEFs were measured using real-time fluorescent quantitative (RTFQ) PCR. The results showed that rhein effectively inhibit NDV activities maximal safe concentration of 0.125 mg/ml. This finding indicated that, rhein could be used as future antiviral drug against NDV.